Increased CD56bright NK cells in HIV-HCV co-infection and HCV mono-infection are associated with distinctive alterations of their phenotype. Issue 1 (December 2016) - Bhardwaj, Suvercha; Ahmad, Fareed; Wedemeyer, Heiner; Cornberg, Marcus; Schulze zur Wiesch, Julian; van Lunzen, Jan; Sarin, Shiv; Schmidt, Reinhold; Meyer-Olson, Dirk
Abstract Background HIV-HCV co-infection is associated with accelerated progression to hepatic fibrosis, cirrhosis and hepatocellular carcinoma than HCV mono-infection. The contribution of innate immunity during HIV-HCV co-infection has been a relatively under-investigated area. Natural killer (NK) cells are pivotal sentinels of innate immunity against viruses and tumour cells. In this study we evaluated the effect of HIV-HCV co-infection on peripheral blood NK cell subsets with emphasis on the phenotype of CD56bright NK cells. Methods Sixty patients were included in the study; HIV mono-infected (n  = 12), HCV mono-infected (n  = 15), HCV-HIV co-infected (n  = 21) and healthy controls (n  = 16). PBMCs were isolated and immunophenotyping of NK cells was performed by flowcytometry. Results We observed an expansion of CD56bright NK cell subset in HIV-HCV co-infection as compared to healthy controls and HIV mono-infected group. All the infected groups had an upregulated expression of the activating receptor NKG2D on CD56bright NK cells in comparison to healthy controls while not differing amongst themselves. The expression of NKp46 in HIV-HCV co-infected group was significantly upregulated as compared to both HIV as well as HCV mono-infections while NKp30 expression in the HIV-HCV co-infected group significantly differed as compared to HIV mono-infection. The CD56bright NK cell subset was activated in HIV-HCV co-infection as assessed by the expression of CD69 as compared to healthy controls but was significantly downregulated in comparison to HIV mono-infection. CD95 expression on CD56bright NK cells followed the same pattern where there was an increased expression of CD95 in HIV mono-infection and HIV-HCV co-infection as compared to healthy controls. In contrast to CD69 expression, CD95 expression in HCV mono-infection was decreased when compared to HIV mono-infection and HIV-HCV co-infection. Finally, expression of CXCR3 on CD56bright NK cells was increased in HIV-HCV co-infection in comparison to HIV mono-infection while remaining similar to HCV mono-infection. Conclusion Thus, HIV-HCV co-infection is able to modulate the phenotype of CD56bright NK cell subset in a unique way such that NKp46 and CXCR3 expressions are distinct for co-infection while both mono-infections have an additive effect on CD56bright, CD69 with CD95 expressions. HCV mono-infection has a dominant effect on NKp30 expression while NKG2D and CD127 expressions remained same in all the groups.